Reflections of the physical education and sports class on the academic achievement of primary school students A field study of some primary schools in the state of Oum El Bouaghi - Algeria - from the perspective of primary education teachers - seddouk, hemza; ferdi, elmoundhir (sports creativity, 2025)
In this study we decided to reveal the impact of the physical education and sports class on the academic achievement of primary school students after a full academic year has passed after the executive decision of the relevant ministry to seek the assistance of specialists, graduates of the physical education institutes of the Algerian university, from the point of view of primary school teachers, to their importance in the educational environment, to know their points of view and direct field observations, and the effects of this educational activity on enhancing children's abilities in all components of the educational and cognitive process. To achieve the set goals, a sample was used that was chosen intentionally, consisting of 56 teachers from the state of Oum El Bouaghi - Algeria, as a model. We also relied on the questionnaire to collect data, and a set of statistical methods were used to analyze it, using the descriptive method to complete the study. The study concluded that physical education and sports classes are more than just a class for physical activity and entertainment for children. It is a class that enhances social relations between students in an educational and pedagogical environment, improves mental abilities while enhancing concentration and understanding, and develops children’s life skills such as problem solving and building a moderate personality in the advanced stages of life. Thanks to the presence of a specialized teacher, these classes have become an opportunity to guide students towards achieving a healthy balance between physical activity and academic achievement, which ensures comprehensive and balanced growth of their personalities and various abilities with the aim of strengthening their physical health and developing their motor, psychological, mental and social behaviours and achieving academic excellence and reaching the highest academic levels